Gender in livestock development: Julie Ojango - Ojango, Julie M.K. (International Livestock Research Institute, 2019)
Julie Ojango, scientists at ILRI, shares her ‘aha’ moment when she really understood the central importance of women in livestock development. This film was produced to mark the International Women’s Day 2019 which is themed ‘Think equal, build smart, innovate for change’.